Procalcitonin Testingreduce Unnecessary Antibiotic Use in Bacterial Infection - Toofani Milani, Attabak; Mohammadian, Mahshid; Rostaminasab, Sadegh; Paribananaem, Roghayeh; Ahmadi, Zohre; Akbarzadeh Khiyavi, Azim (Asian Pacific Journal of Environment and Cancer, 2019)
Conventional diagnostic test have limitations to deferential diagnosis in clinical suspicion ofbacterial infection cases, that in some cases lead to inappropriate antibiotic therapy and increases antibiotic resistance. A new diagnostic insight is procalcitonin (PCT) test to improve diagnosis of bacterial infections and to guide antibiotic therapy. Serum PCT levels are of useful test as a biomarker in patients with bacterial infections for several reasons. Initial rise of PCT levels due to bacterial infection, subsequent sequential PCT levels can be used to assess the effectiveness and duration of antibiotic therapy. Based on clinical researches results, in bacterial infections, promising good results obtained when use of PCT used as differential diagnostic test. But further intervention studies are needed before use of PCT in clinical routine tests. The goal of this review is to study the PCT reliability as infections diagnostic biomarker.